miRNA-loaded exosome-like microparticles as targeted cancer therapy. - Filipovic, Aleksandra; Proklopi, Marianna; Pitsillides, Costas; Kapnisis, Konstantinos; Anayiotos, Andreas; Kousparou, Christina; Epenetos, Agamemnon Anthony (My University, 2016)
Background: Current cancer therapies are partially effective in tumor eradication, due to intrinsic drug resistance as well as failure of therapeutic agents reaching the tumor site. Exosome-like microparticles (MPs) may provide a more efficient way to deliver therapeutics to tumours in a targeted fashion. We have developed improved exosome-like MPs, representing vesicles with relatively uniform size (0.1-1.0 μm), that can be loaded with miRNAs as well as retain their original mesenchymal stem cell (MSC) chemokine profile, allowing them to home into areas of high chemokine expression such as cancer and inflammation. Methods: Exosome-like MPs were released from MSCs of the Wharton's jelly upon cellular stress. Utilizing a state-of-the-art in vitro pharmacokinetics program, with innovative imaging techniques such as in vivoflow cytometry and whole body fluorescence reflectance imaging, we investigated the pharmacokinetic and pharmacodynamic behavior of fluorescently labelled MPs (MP/DiD) containing key anti-cancer miRNAs to define their mode of action and establish safety and efficacy in treating tumors in breast cancer animal models. Results: Exogenously administered MSCs derived exosome-like particles localise within tumor sites where microenvironment resembles inflammation. We used an orthotopic mouse model for breast cancer MDA-MB-231/GFP cells in CD1/nude mice, enabling imaging and assessment of tumor growth in vivo. In vivo flow cytometry of DiD-MPs in tumor-fee mice showed that free, non-internalized MPs were rapidly cleared from circulation, while in vivoimaging demonstrated a reduction in tumor growth over time in mice treated with MPs/DiD compared to untreated mice. Conclusions: Delivery of therapeutic miRNAs via exosome-like MPs affects multiple pathways of cancer development and progression. miRNAs regulate gene expression in cancer cells both through reduction/deletion of oncogenic miRNA and through amplification/overexpression of tumor suppressing miRNA. Thus, compared to earlier approaches targeting single genes, miRNAs delivered in vivo using improved exosome-like particles as vehicles, represent opportunities to target multiple oncogenic molecules in cancer cells offering simultaneously.
Keywords: Cancer therapies; miRNA